Remote Ischemic Preconditioning Ameliorates Acute Kidney Injury due to Contrast Exposure in Rats through Augmented O-GlcNAcylation. (13th August 2018) - Hu, Jiachang; Wang, Yimei; Zhao, Shuan; Chen, Jing; Jin, Shi; Jia, Ping; Ding, Xiaoqiang
Abstract : Remote ischemic preconditioning (RIPC) is an adaptive response, manifesting when local short-term ischemic preconditioning reduces damage to adjacent or distant tissues or organs. O-linked β -N-acetylglucosamine (O-GlcNAc) glycosylation of intracellular proteins denotes a type of posttranslational modification that influences multiple cytoplasmic and nuclear protein functions. Growing evidence indicates that stress can induce an acute increase in O-GlcNAc levels, which can be cytoprotective. The current study aimed to determine whether RIPC can provide renoprotection against contrast-induced acute kidney injury (CI-AKI) by augmenting O-GlcNAc signaling. We established a stable model of CI-AKI using 5/6 nephrectomized rats exposed to dehydration followed by iohexol injection via the tail vein. We found that RIPC increased UDP-GlcNAc levels through the hexosamine biosynthetic pathway as well as global renal O-GlcNAcylation. RIPC-induced elevation of O-GlcNAc signaling ameliorated CI-AKI based on the presence of less tubular damage and apoptosis and the amount of reactive oxygen species. In addition, the use of alloxan, an O-GlcNAc transferase inhibitor, and azaserine, a glutamine fructose-6-phosphate amidotransferase inhibitor, neutralized the protective effect of RIPC against oxidative stress and tubular apoptosis. In conclusion, RIPC attenuates local oxidative stress and tubular apoptosis induced by contrast exposure by enhancing O-GlcNAc glycosylation levels; this can be a potentially useful approach for lowering the risk of CI-AKI.